Bony Landmarks of the Anterior Cruciate Ligament Tibial Footprint: A Detailed Analysis Comparing 3-Dimensional Computed Tomography Images to Visual and Histological Evaluations. (June 2014) - Tensho, Keiji; Shimodaira, Hiroki; Aoki, Tetsuhiro; Narita, Nobuyo; Kato, Hiroyuki; Kakegawa, Akira; Fukushima, Nanae; Moriizumi, Tetsuji; Fujii, Masahiro; Fujinaga, Yasunari; Saito, Naoto
Background: Although the importance of tibial tunnel position for achieving stability after anterior cruciate ligament (ACL) reconstruction was recently recognized, there are fewer detailed reports of the anatomy of the tibial topographic footprint compared with the femoral side. Hypothesis: The ACL tibial footprint has a relationship to bony prominences and surrounding bony landmarks. Study Design: Descriptive laboratory study. Methods: This study consisted of 2 anatomic procedures for the identification of bony prominences that correspond to the ACL tibial footprint and 3 surrounding landmarks: the anterior ridge, lateral groove, and intertubercular fossa. In the first procedure, after computed tomography (CT) was performed on 12 paired, embalmed cadaveric knees, 12 knees were visually observed, while their contralateral knees were histologically observed. Comparisons were made between macroscopic and microscopic findings and 3-dimensional (3D) CT images of these bony landmarks. In the second procedure, the shape of the bony prominence and incidence of their bony landmarks were evaluated from the preoperative CT data of 60 knee joints. Results: In the first procedure, we were able to confirm a bony prominence and all 3 surrounding landmarks by CT in all cases. Visual evaluation confirmed a small bony eminence at the anterior boundary of the ACL. The lateral groove was not confirmed macroscopically. The ACL was not attached to the lateral intercondylar tubercle, ACL tibial ridge, and intertubercular space at the posterior boundary. Histological evaluation confirmed that the anterior ridge and lateral groove were positioned at the anterior and lateral boundaries, respectively. There was no ligament tissue on the intercondylar space corresponding to the intercondylar fossa. In the second investigation, the bony prominence showed 2 morphological patterns: an oval type (58.3%) and a triangular type (41.6%). The 3 bony landmarks, including the anterior ridge, lateral groove, and intertubercular fossa, existed in 96.6%, 100.0%, and 96.6% of the cases, respectively. Conclusion: There is a bony prominence corresponding to the ACL footprint and bony landmarks on the anterior, posterior, and lateral boundaries. Clinical Relevance: The study results may help create an accurate and reproducible tunnel, which is essential for successful ACL reconstruction surgery.